The effectiveness of fixed speed cameras on Iranian taxi drivers: An evaluation of the influential factors - Malekpour, Mohammad-Reza; Azadnajafabad, Sina; Rezazadeh-Khadem, Sahba; Bhalla, Kavi; Ghasemi, Erfan; Heydari, Seyed Taghai; Ghamari, Seyyed-Hadi; Abbasi-Kangevari, Mohsen; Rezaei, Nazila; Manian, Mahmoud; Shahraz, Saeid; Rezaei, Negar; et al. (Frontiers in Public Health, 2022)
Background: The adherence to speed limits can reduce deaths associated with road traffic injuries by more than a quarter. This study aimed to evaluate the effective factors on the speeding behavior of Iranian taxi drivers around fixed speed cameras. Method: Telematics devices used in this study collect the location and speed of the vehicles. The units of analysis in this study were trips per camera, including 2.5 kilometers before and after each camera. Linear regression analysis was used to identify kangaroo driving (KD), defined as trips with a significant V-shape in speed distribution around the camera. In the clustered cameras zone, cameras were placed at regular intervals of approximately 3.5 kilometers. Findings: A total of 93,160 trips were recorded from 13,857,443 data points. There was an inverse association between drivers' age and KD with an odds ratio (OR) of 0.98 (95% Confidence Interval: 0.98-0.98). The intercity trips had a substantially higher probability of KD than urban trips (OR: 4.94 [4.73-5.16]). The tendency of drivers toward KD during the daylight hours versus nighttime was significant for both urban (OR: 1.15 [1.06-1.25]) and intercity (OR: 1.18 [1.14-1.22]) trips. The 4 A.M. to 8 A.M. period had the highest chance of KD in both urban (10.71% [7.41-14.53]) and intercity (44.13% [41.18-47.09]) trips. There was a significant decrease in the odds of KD inside the clustered cameras zone (OR: 0.22 [0.20-0.25]). Conclusion: The heterogeneous occurrence of KD in different locations and times indicates the necessity of evidence-based decision-making in urban planning to improve safe driving behaviors. The lower occurrence of KD in clustered cameras zones could be a practical key to the effective control of speeding behaviors by helping in the efficient placement of cameras through sustainable development of cities and roads.